Women: the key to food security - Quisumbing, Agnes R.; Brown, Lynn R.; Feldstein, Hilary Sims; Haddad, Lawrence J.; Peña, Christine (International Food Policy Research Institute, 1995)
This report, brings together the latest evidence on the key roles that women play in ensuring food security and examines ways to strengthen the three pillars of food security through policies and programs that enhance women's abilities and resources to fulfill their roles.